Mobile Assisted Language Learning (MALL) in English Language Education - Made Hening Ayu Arsari; Sri Sumarni; Darmahusni Darmahusni (Universitas Muhammadiyah Semarang, 2023)
Mobile devices have become essential of our life. Many activities can be done through mobile devices include learning activity. Students can learn by accessing many resources and exercises related their interest. This article purposes to explore the role of mobile assisted language learning which can improve students’ receptive, and productive skills. In this research, the researcher used a systematic review on the used MALL in enhancing students’ English skill. The methodology used was the Preferred Reporting Items and Meta- Analysis (PRISMA) for Systematic Review. The selection articles were taken from reputable journals published between 2018-2022. This study reported MALL has positive effects in enhancing students’ English skills in terms of vocabulary acquisition, reading comprehension, grammar, pronunciation and listening ability. Reflecting on those positive result, it can be concluded that mobile assisted learning has significant effect in enhancing students’ English skills